Faces of inequality : a theory of wrongful discrimination - Moreau, Sophia Reibetanz (New York : Oxford University Press, 2020)
Sophia Moreau argues that although all cases of wrongful discrimination involve a failure to treat some people as the equals of others, these failures are importantly different. She explores the different ways of failing to treat people as equals: through unfairly subordinating some to others, through violating someone's right to a particular deliberative freedom, and through denying some people access to a basic good. The author goes on to explain why these different wrongs can be seen as parts of a coherent theory of wrongful discrimination, and presents some of the explanatory advantages of that this theory has over others. Final chapters argue that the theory enables us to see indirect discrimination as wrongful for many of the same reasons as direct discrimination, and that the duty to treat others as equals is a duty held not just by the state, but also by each individual in society.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on April 28, 2020).
Keywords: Discrimination -- Law and legislation -- Philosophy; Law; Laws of specific jurisdictions & specific areas of law